Nuclear expression of E-cadherin in solid pseudopapillary tumors of the pancreas. - Serra, S; Salahshor, S; Fagih, M; Niakosari, F; Radhi, J; Chetty, R (2007)
CONTEXT: Solid pseudopapillary tumors of the pancreas are rare and have recently been shown to harbor mutations of the beta-catenin gene with resultant nuclear localization of beta-catenin protein to the nucleus. Moreover, there is a close relationship between beta-catenin and E-cadherin. OBJECTIVE: To explore the protein expression of E-cadherin in a series of solid pseudopapillary tumors of the pancreas. PARTICIPANTS: Eighteen cases of solid pseudopapillary tumors of the pancreas. DESIGN: The cases were studied using a tissue microarray that was constructed as follows: for each case, 4 to 14 cores measuring 1.0 mm each were drilled from the blocks. Tissue cores from normal pancreas were used as controls and for orientation purposes. MAIN OUTCOME MEASURES: The slides were stained with the following commercially available antibodies: CD10, CD56, vimentin, alpha-1-antitrypsin, alpha-1-antichymotrypsin, neuron-specific enolase, chromogranin, synaptophysin, beta-catenin and E-cadherin. RESULTS: All the tumors were CD10, vimentin, alpha-1-antitrypsin and alpha-1-antichymotrypsin diffusely positive (50% or more of the tumor cells staining) and CD56 showed focal positivity in all cases with 5-10% of tumor cells displaying immunolabeling. All cases were negative for chromogranin and synaptophysin. All 18 cases displayed cytoplasmic and nuclear localization of beta-catenin protein. Similarly, E-cadherin protein was localized to the nucleus in all 18 cases, with loss of the characteristic membranous decoration of cells. CONCLUSION: This study is the first demonstration of aberrant nuclear localization of E-cadherin protein in solid pseudopapillary tumors of the pancreas. Whilst the exact mechanism is not know and nuclear E-cadherin is not related to tumor aggression, this staining pattern may be of diagnostic value in concert with beta-catenin staining.